Kandungan Kadar Protein Tempe yang Difortifikasi Coriandrum sativum, Alium sativum, dan Amomum cardamomum - Khotimah, Khusnul; Hidayah, Maulida Ulfa; Raihan, Raihan; Windiani, Titi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Tempeh is an affordable source of plant-based protein for the community. The fortification of tempeh with coriander (Coriandrum sativum), garlic (Allium sativum), and cardamom (Amomum cardamomum) is important to study because these three spices contain bioactive compounds that potentially increase the protein content and nutritional value of tempeh. This research is necessary to scientifically examine the effect of spice fortification on tempeh protein levels as an effort to develop functional food. The testing method used in this study was the Kjeldahl method referring to SNI 01-2891-1992. Tempeh fortification with coriander showed the most significant increase in protein content, reaching 7.03%, compared to tempeh without spices, garlic, and cardamom, which only increased protein content to 2.74%, 2.92%, and 3.94%, respectively. This is due to the high protein content in coriander, approximately 17-20% per 100 grams of material, which significantly enriches the protein content of tempeh. In contrast, garlic and cardamom have lower protein content, around 6-7% and 9-11% per 100 grams of material, making their contribution to increasing tempeh protein content less significant. This research demonstrates that the use of coriander as a fortification ingredient can be an effective strategy to enhance the nutritional value and protein content of tempeh, making it a more functional and nutritious choice for consumers.